2011
DOI: 10.1042/bst0390159
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory RNAs in Haloferax volcanii

Abstract: In organisms of all three domains of life, a plethora of sRNAs (small regulatory RNAs) exists in addition to the well-known RNAs such as rRNAs, tRNAs and mRNAs. Although sRNAs have been well studied in eukaryotes and in bacteria, the sRNA population in archaea has just recently been identified and only in a few archaeal species. In the present paper, we summarize our current knowledge about sRNAs and their function in the halophilic archaeon Haloferax volcanii. Using two different experimental approaches, 111 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 46 publications
(62 reference statements)
0
22
0
Order By: Relevance
“…RNomics, bioinformatic predictions coupled to experimental validation and high-throughput sequencing have led to the identification of more than 200 sRNAs in Hfx. volcanii ([30, 39, 113], unpublished results). About 30 deletion mutants of sRNA genes have been constructed, and currently, phenotyping is applied to unravel biological functions of sRNAs in Hfx.…”
Section: Genetics: Application Of Mutants To Characterize Importamentioning
confidence: 99%
“…RNomics, bioinformatic predictions coupled to experimental validation and high-throughput sequencing have led to the identification of more than 200 sRNAs in Hfx. volcanii ([30, 39, 113], unpublished results). About 30 deletion mutants of sRNA genes have been constructed, and currently, phenotyping is applied to unravel biological functions of sRNAs in Hfx.…”
Section: Genetics: Application Of Mutants To Characterize Importamentioning
confidence: 99%
“…H. volcanii is studied as an archaeal model organism because it is easy to cultivate and easily genetically modified 24 - 26 . Recently, RNomics approaches revealed that H. volcanii contains 21 intergenic sRNAs and 18 antisense RNAs 27 - 29 . In this former study only RNAs in the size range of 130–460 nucleotides were analyzed from cells grown only under a single condition.…”
Section: Introductionmentioning
confidence: 99%
“…Driven by the need for more specific and concrete experimental data about SmAP function in vivo, the past 3 y have seen progress on the cellular functions of these proteins, chiefly via proteomic and RNomic detection of interactions between SmAPs and other proteins or RNAs 121 . The basic strategy has been a “guilt by association” approach (e.g., the CLIP-Seq method), 122 wherein the relevant cellular pathways for a protein or RNA of unknown function are inferred based on the co-precipitated binding partners, a subset of which are presumed to have been functionally characterized.…”
Section: Sm Functional Roles In the Archaea: Scaffolds Or Chaperones mentioning
confidence: 99%
“…The basic strategy has been a “guilt by association” approach (e.g., the CLIP-Seq method), 122 wherein the relevant cellular pathways for a protein or RNA of unknown function are inferred based on the co-precipitated binding partners, a subset of which are presumed to have been functionally characterized. Much of this work has been pioneered by Marchfelder and coworkers in the euryarchaeote Haloferax volcanii 96 , 121 , 123 …”
Section: Sm Functional Roles In the Archaea: Scaffolds Or Chaperones mentioning
confidence: 99%